The Meaning of Jesus Washing the Feet of His Disciples (John 13) - Watt, Jan Gabriël van der (Neotestamentica, 2017)
Jesus washes the feet of his disciples and consequently explains to them that his action should serve as an example to them. It is common in Johannine studies to interpret the meaning of Jesus' action as a willingness to humble himself in service of other believers, based on the fact that slaves usually washed the feet of guests, marking it as an action reserved for people of lower status. In this article the question is addressed whether this is indeed the correct interpretation of what Jesus did. The conclusion is that the abovementioned interpretation does not correctly or fully reflect the meaning of Jesus' action of love, but that the emphasis falls on the nature of intense love.